Avaliação clínica da relação entre o índice de placa, índice gengival, alinhamento dental, mucosa ceratinizada, tipo de periodonto e distúrbios oclusais com a ocorrência de recessão gengival - Farias Neto, Eudivar Correia de (2010)
This study clinically evaluated the relationship of gingival recessions with the periodontal index of gingival and plaque, dental alignment, keratinized mocous, type of periodontal, and occlusal disorders. Study participants were individuals aged between 19 and 33 years. The evaluations were performed by using questionnaires and clinical examinations. In subjects examined, the teeth were assessed and divided into groups (Molars, premolars, canines and incisors). The gingival recession were measured in the central region of the teeth and individuals were subject to disclosure to the plate and observing the poll of plaque and gingival index, respectively. 558 teeth were examined, with 24.1%, 135 had gingival recession greater than or equal to 1mm. Through the combination of tests used to evaluate the average of the recession and its relationship with the variables studied, we observed that the degree of recession of the elements assessed dental showed, almost for the most part, when higher values associated with the index plaque (p = 0.101), Gingival Index (p = 0.053), dental alignment (p = 0.962), width of keratinized mocous (p = 0.004) and type of periodontium (p = 0.033), however statistically significant difference could only be considered when related the recessions in the keratinized mocous and the type of the periodontium. Although we identify, when we evaluate the whole set of teeth that occlusal disturbances (p = 0.002) were more strongly associated with cases of gum recession that the gingival index (p = 0.006), however, these two conditions were correlated with the cases of recession, contributing to its occurrence